Exclusivity: Research in Practice – Interview with Professor Gilbert Herdt - Abidin, Crystal (University of Western Australia, 2013)
In early 2013, Crystal Abidin had the opportunity to interview Gilbert Herdt, Professor and Director of the Human Sexuality PhD Programme at The California Institute for Integral Studies in San Francisco. Prof. Herdt is well known for his work on the ‘Sambia’ people (a pseudonym) of Papua New Guinea, having traced the sexual phrases of males and their creation of sexual meanings and practices. His current research focuses on Sexual Orientation, Marriage Rights, and LGBTQ Youth, and how research and policy are helping young people’s lives.